Exploring Food Decision Making in Polycystic Ovary Syndrome (PCOS) Through the Listening Guide - S. Herbert; C. Gilligan; A. Squires; K. Woolf (Journal of the Academy of Nutrition and Dietetics, 2024)

Feasibility and Tolerability of Daily Microgreen Consumption in Healthy Middle-Aged/Older Adults: A Randomized Crossover Trial - S. Holmes; K. Michell; M. Butler; B. Smith; A. Vazquez; E. Woolf; L. Grabos; S. Lee; S. Newman; M. Uchanski; T. Weir; S. Johnson (Journal of the Academy of Nutrition and Dietetics, 2023)

An Inter-professional Plant-based Culinary Medicine Program for Nutrition and Medical Students - L. Castro; S. Joshi; M. McMacken; K. Woolf (Journal of the Academy of Nutrition and Dietetics, 2023)

Ocean carbon from space: Current status and priorities for the next decade - Robert J.W. Brewin; Shubha Sathyendranath; Gemma Kulk; Marie-Hélène Rio; Javier A. Concha; Thomas G. Bell; Astrid Bracher; Cédric Fichot; Thomas L. Frölicher; Martí Galí; Dennis Arthur Hansell; Tihomir S. Kostadinov; et al. (Earth-Science Reviews, 2023)

A Systematic Review and Meta-Analysis of Cognitive Training in Adults with Major Depressive Disorder - C. Woolf; A. Lampit; Z. Shahnawaz; J. Sabates; L. M. Norrie; D. Burke; S. L. Naismith; L. Mowszowski (Neuropsychology Review, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Diltiazem Promotes Regenerative Axon Growth - Eric A. Huebner; Stéphane Budel; Zhaoxin Jiang; Takao Omura; Tammy Szu-Yu Ho; Lee Barrett; Janie S. Merkel; Luis M. Pereira; Nick A. Andrews; Xingxing Wang; Bhagat Singh; Kush Kapur; et al. (Molecular Neurobiology, 2019)

Toxicants in folk remedies: implications of elevated blood lead in an American-born infant due to imported diaper powder - Mateusz P. Karwowski; Suzette A. Morman; Geoffrey S. Plumlee; Terence Law; Mark Kellogg; Alan D. Woolf (Environmental Geochemistry and Health, 2017)

Examining the Origins of the Hydration Force Between Lipid Bilayers Using All-Atom Simulations - Anastasia N. Gentilcore; Naveen Michaud-Agrawal; Paul S. Crozier; Mark J. Stevens; Thomas B. Woolf (The Journal of Membrane Biology, 2010)

Genetic analyses reveal a requirement for Dicer1 in the mouse urogenital tract - Laura M. Pastorelli; Sara Wells; Martin Fray; Adrian Smith; Tertius Hough; Brian D. Harfe; Michael T. McManus; Lee Smith; Adrian S. Woolf; Michael Cheeseman; Andy Greenfield (Mammalian Genome, 2009)

A molecular and genetic analysis of renalglomerular capillary development - Siobhan Loughna; Patricia Hardman; Ellie Landels; Lotta Jussila; Kari Alitalo; Adrian S Woolf (Angiogenesis, 1997)

Differences in the metabolism of the aromatic amino acid hydroxylase cofactor, tetrahydrobiopterin, in mutant mice with neurological and immunological defects - David S. Duch; Seaton W. Bowers; Jeffrey H. Woolf; Muriel T. Davisson; Lois J. Maltais; Charles A. Nichol (Biochemical Genetics, 1986)

Potato notes - Lou D. Sweet; J. H. Woolf; A. E. Wilkinson; F. C. Gaylord; E. A. Stodyke; R. D. Hews; H. C. Moore; J. W. Weston; W. V. Longley; J. Norton Woodruff; W. H. Martin; J. C. Crissey; et al. (American Journal of Potato Research, 1924)